Influence of oxide layers on optical properties of copper in a wide spectral range - Filipov, Y.V.; Staschuk, V.S.; Poperenko, L.V. (Functional Materials, 2005)
Optical properties of flawless bulk copper sample has been studied based on spectroel-lipsometry measurements in a wide spectral interval (Av = 0.18 to 4.87 eV) at various angles of light incidence. The main characteristics of electronic subsystem of this metal and values of main energy intervals in a band structure have been calculated. Taking into consideration influence of the surface oxide layer. Исследованы оптические свойства массивных образцов меди с идеальной структурой на основе спектроэллипсометрических измерений в широкой области спектра (Av = 0.18-4.87 эВ) при различных углах падения света. Рассчитаны характеристики электронной подсистемы металла и основные энергетические интервалы зонной структуры медных образцов с учетом влияния поверхностного слоя окиси. Досліджено оптичні властивості масивних мідних зразків з ідеальною структурою на основі спектроеліпсометричних досліджень у широкій області спектру (hv = 0.18-4.87 еВ) при варіюванні кута падіння світла. Розраховано характеристики електронної підсистеми металу та основні енергетичні інтервали зонної структури мідних зразків з урахуванням впливу приповерхневого шару оксиду.